Analisis Implementasi Adopsi E-Commerce Berdasarkan Model of Internet Commerce Adoption (MICA) dan Theory of Planned Behavior (TPB) - Sundari, Siti (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2022)
This study aims to determine the level of e-commerce adoption based on the Model of Internet Commerce Adoption (MICA) and the implementation of e-commerce adoption based on Theory Planned Behavior (TPB). The research method used is qualitative analysis. Based on the results of the study, it was concluded that the level of e-commerce adoption carried out by the Sukahijab Micro, Small and Medium Enterprises (MSMEs) had fulfilled the third stage and reached the third stage of completing the features at each stage not completing everything. Referring to the Theory Planned Behavior (TPB) it turns out that not all of them are the same as what was stated by Azjen. There is one different factor, namely the Subjective Norm. Where in the Sukahijab UMKM itself, subjective norms have no effect, where the surrounding environment has no effect to provide encouragement in the implementation of the e-commerce. The most influential of the three factors is Attitude Toward the Behavior, then Perceived Behavioral Control, and the least influential is Subjective Norm